2013
DOI: 10.5603/fm.2013.0040
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the hand extensors

Abstract: This study was performed to investigate the anatomy and variations of the human ' data. (Folia Morphol 2013; 72, 3: 249-257)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…The EPB could be missing in 7.6% (Shigematsu et al, ), in 2.1% (Abdel‐Hamid et al, ), in 0% (Nayak et al, ; Kulshreshtha et al, ), in 2% (Jackson et al, ; Joshi and Joshi, ), in 3.75% (Brunelli and Brunelli, ), in 6.2% (Dawson and Barton, ), and in 5.5% (Wood, 1867, 1868). The average absence frequency is 2.7%.…”
Section: Resultsmentioning
confidence: 99%
“…The EPB could be missing in 7.6% (Shigematsu et al, ), in 2.1% (Abdel‐Hamid et al, ), in 0% (Nayak et al, ; Kulshreshtha et al, ), in 2% (Jackson et al, ; Joshi and Joshi, ), in 3.75% (Brunelli and Brunelli, ), in 6.2% (Dawson and Barton, ), and in 5.5% (Wood, 1867, 1868). The average absence frequency is 2.7%.…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐two duplicates were removed and initial screening of the remaining 644 articles yielded 104 potentially relevant, of which 18 narrative reviews and 68 clinical or cadaveric case reports were excluded. References cited in the remaining 18 articles yielded another six relevant studies; so in total, we located 24 cadaveric studies reporting the prevalence of at least one of the primary outcomes (Mori, ; Schenk, 1964; el‐Badawi et al, ; Mestdagh et al, ; Godwin and Ellis, ; Wehbe, ; el‐Badawi et al, ; von Schroeder and Botte, ; Gonzales et al, , ; Komiyama et al, ; Hirai et al, ; Zilber and Oberlin, ; Tanaka et al, ; Celik et al, ; Ranade et al, ; Jeon et al, ; Agarwal and Tirthani, ; Bolwar, ; Dass et al, ; Govsa et al, ; van Aken et al, ; Yoo et al, ; Abdel‐Hamid et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies reported the prevalence of EDC‐II (Mori, ; Mestdagh et al, ; Godwin and Ellis, ; El‐Badawi et al, ; von Schroeder and Botte, ; Gonzales et al, ; Komiyama et al, ; Hirai et al, ; Zilber and Oberlin, ; Celik et al, ; Ranade et al, ; Agarwal and Tirthani, ; Bolwar, 2011; Dass et al, ; Abdel‐Hamid et al, ) with a total of 2,005 hands and a PPE of 99.8%. The pooled prevalences were 98% (95% CI = 0.960–0.993, I 2 = 85.5%), 1.8% (95% CI = 0.005–0.038, I 2 = 85.1%), and 0.2% (95% CI = 0.0004–0.004, I 2 = 0%) for the single, double, and triple EDC‐II slips, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations